Understanding the role of technology within a Community of Practice of small businesses - Peters, Sue (Proceedings of the International Conference on Networked Learning, 2008)
This paper reports the results of an ethnographic study into the use of an online forum which supports a Community of Practice (CoP) of owner-managers of small to medium sized enterprises (SMEs) engaged in a leadership programme (LEAD). The paper outlines the research focus, the methodology and the theoretical frameworks underpinning these as well as highlighting some of the key findings. This paper draws upon CoP theory and the sociology of technology to understand how the LEAD forum helped to construct and maintain LEAD as a CoP. There is little written on both the social construction of technology and CoP in relation to SMEs and this paper contributes to these debates. The four key findings show that firstly, LEAD is a CoP and the online forum helped to provide the glue which acted as community maintenance. Secondly, the online forum is a social space that did not work for individual reflection. Thirdly, researching the CoP as a member of one has methodological implications invoking the need for reflexivity. Lastly, the practice of using the online forum was taken and translated into other contexts with limited success. Issues of power relations between the SME owner managers within their own organisations (which may or may not be considered as a CoP) are also discussed. This paper will be of interest to academics and practitioners alike who have an interest in social technologies in the workplace, SMEs and debates surrounding CoP and the sociology of technology.